Analisis Komoditas Unggulan Subsektor Perkebunan di Kabupaten Bandung dan Peluang Pasar Internasional - Muzakki, Muhammad Farhan Nurhamzah; Mukti, Gema Wibawa (Universitas Galuh, 2025)
The plantation sub-sector commodities are primarily export-oriented. Each region possesses distinct plantation commodities shaped by its unique geographical characteristics. Therefore, the local government of Bandung Regency must identify its leading plantation commodities along with their potential in the international market. This study aims to identify the leading plantation sub-sector commodities in Bandung Regency and assess their opportunities in global trade. The study utilizes time-series data from 2019 to 2023, sourced from UN Comtrade and Statistics Indonesia (BPS). To determine the leading commodities, the Location Quotient (LQ) and Differential Shift (DS) methods were employed. Furthermore, the Revealed Comparative Advantage (RCA) and Export Product Dynamics (EPD) approaches were used to evaluate the competitiveness and market position of these commodities in international trade. Finally, the X-Model Potential Export Product framework was applied to explore export development opportunities. The findings indicate that coffee and tobacco are the leading plantation commodities in Bandung Regency. These commodities exhibit comparative advantage but lack competitiveness, placing them in a